Seasonal reproductive endothermy in tegu lizards - Tattersall, Glenn J.; Leite, Cleo A. C.; Sanders, Colin E.; Cadena, Viviana; Andrade, Denis V. [UNESP]; Abe, Augusto S. [UNESP]; Milsom, William K. (American Association for the Advancement of Science (AAAS), 2016)
With some notable exceptions, small ectothermic vertebrates are incapable of endogenously sustaining a body temperature substantially above ambient temperature. This view was challenged by our observations of nighttime body temperatures sustained well above ambient (up to 10°C) during the reproductive season in tegu lizards (~2 kg). This led us to hypothesize that tegus have an enhanced capacity to augment heat production and heat conservation. Increased metabolic rates and decreased thermal conductance are the same mechanisms involved in body temperature regulation in those vertebrates traditionally acknowledged as true endotherms: the birds and mammals. The appreciation that a modern ectotherm the size of the earliest mammals can sustain an elevated body temperature through metabolic rates approaching that of endotherms enlightens the debate over endothermy origins, providing support for the parental care model of endothermy, but not for the assimilation capacity model of endothermy. It also indicates that, contrary to prevailing notions, ectotherms can engage in facultative endothermy, providing a physiological analog in the evolutionary transition to true endothermy.